Job and family demands and burnout among healthcare workers: The moderating role of workplace flexibility. (June 2021) - Maglalang, Dale Dagar; Sorensen, Glorian; Hopcia, Karen; Hashimoto, Dean M.; Katigbak, Carina; Pandey, Shanta; Takeuchi, David; Sabbath, Erika L.
Abstract: Burnout is a growing problem among healthcare workers. Whereas there are numerous predictors of burnout, this article explores the compounding effects of job and family demands among nurses and Patient Care Associates (PCA). This study used the 2018 survey data of the Boston Hospital Health Workers Study (BHWHS) to assess the relationship of job and family demands, workplace flexibility, and burnout (N = 874). In addition, it aimed to evaluate the moderating effect of workplace flexibility and job and family demands on burnout. Results of the study demonstrate that active and high strained healthcare workers are associated with higher odds of experiencing burnout as well as workers who reported perceived low workplace flexibility. In addition, workplace flexibility is associated with reduced odds of experiencing burnout. Workplace flexibility moderated the relationship of childless married healthcare workers and burnout. The study shows that workplace flexibility plays a critical role in potentially reducing odds of burnout in the healthcare worker population. Assessing the perception and accessibility to workplace flexibility among workers is imperative to improve worker well-being and the quality of care provided to patients especially the current effects to worker's health during a pandemic. Highlights: Burnout is an increasing concern among healthcare workers. We examined the buffering effects of workplace flexibility on the compounding effects of job and family demands on burnout. Workplace flexibility is associated with lower odds of burnout. Healthcare workers who are categorized as active and high-strained are associated with higher odds of burnout. Workplace flexibility moderated the relationship of married healthcare workers without children and burnout.